Analisis Perbedaan Abnormal Return, Aktivitas Volume Perdagangan, Bid-Ask Spread Sebelum Dan Sesudah Pandemi Virus Corona Terkonfirmasi Di Indonesia - Wila Mainika Putri; Baiq Kisnawati; M. Wahyullah (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This research aims to determine the differences in abnormal returns, trading volume activity and bid-ask spread before and after the corona virus pandemic was confirmed in Indonesia for all companies included in the Jakarta Islamic index. The population in this study are all companies that are members of the Jakarta Islamic index. Sampling using saturated sample technique. The method used is different test analysis with an observation period of 11 days, namely t = -5 (5 days before the corona virus pandemic was confirmed in Indonesia), t = 0 (1 day when the corona virus pandemic was announced), t = +5 (5 days after the announcement of the coronavirus pandemic). Testing is carried out using the Paired Sample T-Test for data that is normally distributed and the Wilcoxon Signed Rank Test for data that is not normally distributed. Based on the research results, it was found that there were no differences in abnormal returns, trading volume activity and bid ask spread before and after the corona virus pandemic was confirmed in Indonesia.